On Religious and Cultural Principles of Environmental Protection - Sadowski, Ryszard F. (Problemy Ekorozwoju, 2020)
The influence of religion on the human attitude to nature has been a thoroughly studied issue over the last sixty years. The present paper addresses a particular aspect of this issue, namely, it provides a comparison of religious and cultural principles characterizing animistic religions and Christianity. It also concentrates on the ecological consequences of supplanting animism with Christianity. The results of the conducted research indicate that the role of religious and cultural principles standing guard over nature is usually either overestimated or depreciated. Religion may only become an important ally making a real contribution to nature conservation at both local and global levels, providing that those principles are attributed their proper significance.